2013
DOI: 10.1002/j.0022-0337.2013.77.1.tb05441.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Supernumerary Teeth in 2D and 3D: Review of Literature and a Proposal

Abstract: Supernumerary teeth occur in both syndromic and nonsyndromic patients, and dental professionals are likely to encounter such teeth in their professional careers. There are three main numbering systems used to identify teeth today: the Universal/ National, the Palmer/Zsigmondy notation, and the Federation Dentaire Internationale (FDI) numbering systems. However, a review of the literature suggests that none of these three consistently addresses the identiication of supernumerary teeth. Being able to communicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…There are different opinions about the treatment options of ST.[ 5 ] Some authors suggested that if ST do not cause any discernable adverse effect on adjacent teeth and if no future orthodontic treatment foreseen, it is reasonable to recommend that immediate surgical intervention is not essential. [ 70 71 ] Other suggested that ST have a tendency to resorb and disappear if left untreated. [ 72 73 ] Treatment decision may affected from several factors, such as the ST are erupted or nonerupted, stage of the crown and root development, the distance between the ST and root of the adjacent teeth and the condition of the dentition (malocclusion, crowding, missing teeth).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different opinions about the treatment options of ST.[ 5 ] Some authors suggested that if ST do not cause any discernable adverse effect on adjacent teeth and if no future orthodontic treatment foreseen, it is reasonable to recommend that immediate surgical intervention is not essential. [ 70 71 ] Other suggested that ST have a tendency to resorb and disappear if left untreated. [ 72 73 ] Treatment decision may affected from several factors, such as the ST are erupted or nonerupted, stage of the crown and root development, the distance between the ST and root of the adjacent teeth and the condition of the dentition (malocclusion, crowding, missing teeth).…”
Section: Discussionmentioning
confidence: 99%
“…[ 72 73 ] Treatment decision may affected from several factors, such as the ST are erupted or nonerupted, stage of the crown and root development, the distance between the ST and root of the adjacent teeth and the condition of the dentition (malocclusion, crowding, missing teeth). [ 70 71 72 ]…”
Section: Discussionmentioning
confidence: 99%
“…The second goal is to detail the morphology of the supernumerary teeth. Information derived from CBCT images of unerupted supernumerary teeth could facilitate decisions on which of the teeth to retain, determination of the retrievability of those teeth and mapping the optimal surgical access to the teeth, 51 as illustrated in the example in Figure 6.…”
Section: Utilization Of Cbct For Orthodontic Treatment Outcomes Diagmentioning
confidence: 99%
“…Morphologically, they are conical (approximately two thirds of the cases), which makes eruption in the oral cavity easier, and contributes to surgical removal 12 . However, they can appear with tuberculate or molariform aspect 13 . The mesiodens can be vertically positioned, either in normal or inverted form, at risk of erupting in the nasal cavity, or in horizontal position 14 .…”
Section: Clinical Casementioning
confidence: 99%